Problems Encountered in the Process of Translation and their Possible Solutions: The Point of View of Students of Technical Translation - Roskoša, Antra; Rūpniece, Diāna (Vertimo studijos, 2019)
This research investigates the opinions of novice translators–35 students of the Institute of Applied Linguistics, in Bachelor’s and Master’s Programmes of Technical Translation at Riga Technical University–regarding the problems encountered while translating. Data for the research were drawn from the students’ essays and then explored using content analysis. According to the views of technical translation students, knowledge of the type and nature of translation problems helps the translator solve them and provide adequate, quality translations.